2021
DOI: 10.1177/21533687211007548
|View full text |Cite
|
Sign up to set email alerts
|

“Blacks Can’t Jump”: The Racialization of Transit Police Responses to Fare Evasion

Abstract: This study demonstrates that racially disparate fare evasion citation outcomes are the product of racialized social systems that allow transit police officers to determine the belongingness of Black riders in systems of mass transit. Using citation data from the Washington Metropolitan Area Transit Authority, we test the impact of race and place attributes on transit officer decisions to allocate punishment for subway fare evasion using mixed effects logistic regression controlling for individual and contextua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…Research has shown that Black and Latinx populations face disproportionate police contact and prosecutorial overcharging. “Order Maintenance Policing” regularly occurs in areas with higher concentrations of Black and Latinx people, resulting in disparate arrest outcomes for these populations (American Civil Liberties Union, 2013; Beckett et al, 2005, 2006; Carter & Johnson, 2021; Geller, 2016; Geller & Fagan, 2011). In the courtroom, Black defendants are also more likely to face more serious charges and less likely to have their charges dropped and case dismissed (Berdejó, 2017; Lynch & Omori, 2018; Petersen & Omori, 2020; Rosenberg et al, 2017; Sutton, 2013).…”
Section: Patchwork Disclosure: a Modern Form Of Inequality?mentioning
confidence: 99%
“…Research has shown that Black and Latinx populations face disproportionate police contact and prosecutorial overcharging. “Order Maintenance Policing” regularly occurs in areas with higher concentrations of Black and Latinx people, resulting in disparate arrest outcomes for these populations (American Civil Liberties Union, 2013; Beckett et al, 2005, 2006; Carter & Johnson, 2021; Geller, 2016; Geller & Fagan, 2011). In the courtroom, Black defendants are also more likely to face more serious charges and less likely to have their charges dropped and case dismissed (Berdejó, 2017; Lynch & Omori, 2018; Petersen & Omori, 2020; Rosenberg et al, 2017; Sutton, 2013).…”
Section: Patchwork Disclosure: a Modern Form Of Inequality?mentioning
confidence: 99%
“…Inequitable mobility hinders accessing health care, employment, education, exercise, and nutritious food, thereby affecting physical and mental health, relationships, and economic security 1,3–9. Infrastructure and policies to improve mobility often advantage the privileged,1,3–9 and policies such as helmet laws10 and transit enforcement11–13 are disproportionately used against people of color. Residential segregation that separates racial/ethnic groups within a geographic area creates health disparities and inequitable access to safe and quality sidewalks, bikeways, public transportation routes, green space, and other built environment amenities 1,14–17.…”
mentioning
confidence: 99%
“…While persistent discrimination in institutional settings such as the labor and housing market has long been documented (Auspurg et al, 2019;Pager & Shepherd, 2008;Zschirnt & Ruedin, 2016), field research showing everyday discrimination in more informal, unstructured encounters has only recently been gaining traction (Aidenberger & Doehne, 2021;Baldassarri, 2020;Choi et al, 2021bChoi et al, , 2021aKoopmans & Veit, 2014;Zhang et al, 2019Zhang et al, , 2022. There is already evidence that law enforcement targets free-riding by outgroup members more so than by ingroup members, due to so-called 'ethnic profiling' (Carter & Johnson, 2021;Mujcic & Frijters, 2020). As a high-profile example, it recently came to light that the Dutch government targeted citizens with an ethnic-minority background more so in controls for free-riding than citizens with a native-majority background (tax evasion in particular; European Parliament, 2022).…”
Section: Discussionmentioning
confidence: 99%